Alkaline basalts in the Karamay ophiolitic mélange, NW China: A geological, geochemical and geochronological study and implications for geodynamic setting. (1st December 2015) - Yang, Gaoxue; Li, Yongjun; Santosh, M.; Xiao, Wenjiao; Yang, Baokai; Tong, Lili; Zhang, Shenglong
Graphical abstract: Highlights: Alkaline basalts from Karamay ophiolitic mélange characterized with OIB affinity. The rocks were derived from a Middle Devonian mantle plume-related source. The plume-related activity in the CAOB was generally continuous during the development of the Paleo-Asian Ocean. Abstract: Alkaline basalts are common constituents in many ophiolite belts and accretionary complexes. Here we report geological, geochronological, geochemical, and whole-rock Sr–Nd isotopic data for alkaline basalts from the Karamay ophiolitic mélange of West Junggar, southern Central Asian Orogenic Belt (CAOB). In the ophiolitic mélange, imbricate thrusts, duplexes, "web" structures, pinch-and-swell structures, tilted structures in pillow metabasalts, and shear band cleavages are widely developed. U–Pb analyses of zircon grains from a representative basalt by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) yielded crystallization age of ca. 395 ± 3 Ma, suggesting formation during the Middle Devonian. Geochemically, all the samples bear the signature of ocean island basalt (OIB), and are characterized by alkaline affinity with high concentrations of Na2 O + K2 O (4.22–7.28 wt.%) and TiO2 (1.72–2.89 wt.%), LILE and LREE enrichment and HREE depletion ((La/Yb)N = 8.4–15.6), with very strong or no Eu anomalies (Eu/Eu * = 0.6–1.1), and no obvious Nb, Ta or Ti negative anomalies. The rocks display consistent Sr–Nd isotopic compositions (initial 87 Sr/ 86 Sr ratios = 0.70326–0.70453, ε Nd( t ) = + 3.1–+7.6). The results suggest that all the alkaline basalts were derived from a mantle plume-related source in an intra-oceanic setting with ca. 1–3% degree partial melting of garnet lherzolite. These observations, in combination with previous work, indicate that the alkaline basalts from Karamay ophiolitic mélange can be correlated to a Middle Devonian mantle plume-related magmatism within Paleo-Asian Ocean. We further suggest that the plume-related activity in the CAOB was generally continuous during the development of the Paleo-Asian Ocean.